Health Education on Diabetes Prevention for Family Empowerment and Welfare Women in Lembah Griya Indah Citayam - Jatmiko, Najla Qonita Putri; Jannah, Wirdatul; Apriningsih (Salus Publica: Journal of Community Service, 2025)
Diabetes mellitus (DM) is a metabolic disease characterized by an increase in human blood sugar levels. Apart from that, an unhealthy lifestyle can also be a cause of diabetes mellitus. Unhealthy lifestyles can include lack of sleep, lack of physical activity such as exercising, not consuming enough fiber, and others. The number of cases of diabetes mellitus continues to increase every year. This can result because many people prefer food and drinks that contain quite a lot of sugar in them. West Java Province recorded an increase in the incidence of diabetes mellitus from 2019 to 2020, from 790,686 diabetes mellitus sufferers in 2019 to 1,218,294 in 2020. The regional health profile of Bogor City recorded that in 2017, 27,000 people were suffering from diabetes mellitus which then increased in 2020 to 71,462 people suffering from diabetes mellitus. This community service aims to provide education to PKK mothers regarding diabetes mellitus which includes definitions, symptoms, and prevention efforts using poster media. This community service was carried out on 10 respondents who were PKK mothers at the Lembah Griya Citayam Housing Complex. This activity uses a pre-test and post-test design which aims to determine differences in the level of knowledge of respondents regarding diabetes mellitus before and after the education was carried out. The statistical test used in this activity is the Paired Sample T-test. The test results show that poster education media with a p-value = 0.000 (p < 0.05) has a significant influence on increasing the level of knowledge of PKK mothers regarding diabetes mellitus. So it can be concluded that poster media is effective in increasing PKK mothers' knowledge about diabetes mellitus